Analisis Potensi Air Tanah di Kabupaten Gowa Provinsi Sulawesi Selatan - Ichsan Invanni Baharuddin; Nasiah Badwi; Sulaiman Zhiddiq (Universitas Negeri Makassar, 2023)
This study aims to describe the potential of groundwater in Gowa Regency. The methods used are: Remote Sensing and Geographic Information Systems. There are 6 variables overlayed in this study, namely: Rainfall, Rock Type, Slope, Soil Type, Vegetation Density, and Land Use. The results showed that there are five classes of groundwater potential, namely: very low, low, medium, high, and very high. Most of the area is in the high class covering an area of 97,357.47 Ha (53.96 percent) spread throughout the sub-district. The class of groundwater potential is very high covering an area of 44,880.89 Ha (24.87 percent) spread across 17 districts. The variables that determine the high and low groundwater potential in an area are mutually combined between variables but the most dominant are: Rainfall, rock type, and land use.